Complete genome sequence of a sub-subgenotype 2.1i isolate of classical swine fever virus from China - Zhang, B.; Mi, S.; Bao, F.; Guo, H.; Tu, C.; Shi, Jishu; Gong, W. (My University, 2017)
The complete genome sequence of a sub-subgenotype 2.1i isolate of classical swine fever virus (CSFV), GD317/2011, was determined. Notably, GD317/2011 is distant from the sub-subgenotype 2.1b isolate HEBZ at genes of Erns, E1, E2, P7, NS2, NS5A and the 3=-nontranslated region (3=-NTR) but is closely related to that at genes of Npro, Core, NS3, NS4A, NS4B, and NS5B. © 2017 Zhang et al.
Citation: Zhang, B., Mi, S., Bao, F., Guo, H., Tu, C., Shi, J., & Gong, W. (2017). Complete genome sequence of a sub-subgenotype 2.1i isolate of classical swine fever virus from China. Genome Announcements, 5(14). doi:10.1128/genomeA.00127-17